Kirkekamp på Østerbro: Om Socialdemokratiet og Kirkefondet i mellemkrigstiden - Andersen, Lars (Kirkehistoriske Samlinger, 2015)
Det københavnske Kirkefonds store indsamlinger til kirkebyggeri i midten af 1920’erne bragte fondet på konfliktkurs med den socialdemokratiske regering. Kirkeminister P. Dahl rejste kritik af Kirkefondets ejendomsret til kirkerne samt retten til ”den halve brug af kirken”, der gav Kirkefondet mulighed for at ansætte en valgmenighedspræst til den halve brug af kirken, selv om denne var overdraget til folkekirkelig brug. Denne artikel undersøger konflikten mellem Dahl og Kirkefondet, belyst ud fra en kirkeindvielse og en sogneudskillelse på Østerbro, hvor Aldersro Sogn og Sions Sogn i 1926 fik socialdemokratisk flertal i menighedsrådene. Kirkefondet var på den ene side en meget effektiv indsamlingskomite i mellemkrigstiden, men kirkehistorikerne har hidtil overset, at konflikten på Østerbro samtidig afspejlede Kirkefondets aftagende kirkepolitiske indflydelse i København. The Church battle of Østerbro, Copenhagen The social democrats and The Copenhagen Church Building Fund in the interwar period The Copenhagen Church Building Fund was formed in 1896 as a joint venture between lay volunteers and the ecclesiastical authorities. The Church Building Fund raised money for the building of numerous churches and they formed active congregations around these churches. The Church Building Fund occupied an exceptional position in the Danish national church in two ways. First of all they owned the churches whereas the majority of Danish churches were independent. Secondly, The Church Building Fund for each of their churches had the right to appoint an additional clergyman of their choice, regardless of the wishes amongst the majority of the parishioners. In the 1920’s a conflict broke out between the social democratic government and The Church Building Fund. P. Dahl, the minister of ecclesiastical affairs, argued that the rights of The Church Building Fund were incompatible with the democratic ecclesiastical legislation of the 20th Century. When The Church Building Fund refused to revoke these rights, Dahl encouraged the labour population to vote for social democratic candidates for the parochial church council election of 1926. The social democrats got the majority of votes in two neighboring parishes in Copenhagen and for the next four years Dahl and the majority of the two parochial church councils fought The Church Building Fund. The Fund argued that the exceptional position in the national Danish church was needed in order to protect the core of its contributors – the strictly devoted minority of parishioners – from the “half-hearted Christian majority”. The social democrats argued that the church building in the 1920’s was increasingly financed by all parts of the population and not only the strictly devote Christians. The Social Democratic Party had adopted a more positive attitude towards the national church, and every parishioner should have an equal saying in the churches. The conflict reached its climax when a new parish, “Kildevæld” was to be separated from the two social democratic dominated parishes, “Aldersro” and “Sion”. The Church Building Fund was led by strong characters, such as professor of economics Harald Westergaard, the rural dean Henry Ussing and pastor P. Helweg-Larsen. In 1930 they managed to obtain special ecclesiastical rights for the newly planned parish church in Kildevæld, much to the dissatisfaction of social democrats. The general interpretation among church historians is that The Church Building Fund in 1930 defeated the social democrats and the Ministry of Ecclesiastical Affairs. But this article argues that it was a pyrrhic victory. The new parish church of Kildevæld was consecrated in accordance with the traditional congregational and ecclesiastical values of The Church Building Fund. But the struggle at the same time revealed that the former strong tie between the board of The Church Building Fund and the local committee’s and congregations was in fact impaired. At the local level people usually supporting The Church Building Fund were beginning to question the strong authority of The Church Building Fund. The board was left with strong legal rights but seemingly diminishing spiritual ones. By deliberate strategic moves, the social democratic minister of ecclesiastical affairs, P. Dahl, actually managed to display The Church Building Fund as an isolated organization. It no longer held the strong central authority in Copenhagen. The future belonged to the parochial church councils and church democracy. These events in fact pre-empted the final dissolution of the exceptional position of The Church Building Fund in 1940. Nevertheless, The Church Building Fund continued to finance and raise churches in the following decades. But each church was now subordinate to the ecclesiastical legislation equal to any other parish church in the Danish national church.